Depresión y su afectación en las relaciones sociales de una adolescente de 16 años de edad con problemas familiares - Freire Lopez, Gafter Estefania (2022)
The following study work aims to determine the effects of depression on the social relationships of a 16-year-old adolescent with family problems through the use of psychological techniques in order to improve the quality of life in mental health. Given the isolation and episodes of frequent crying for no reason, which alter their social relationships and the concern on the part of the collaborators of the school, this case was referred to a professional in psychology, so that it could be evaluated, to treat this case it was used various techniques and instruments such as; observation, clinical history, interview, Hamilton and Rosenberg tests, determining that the adolescent presented a Major Depressive Disorder, it should be emphasized that the depression detected had been developing from the problems with her mother, who from the problems and Little relationship with her mother, having emotional problems ever since. To work on this patient, psychotherapy was started through CBT Cognitive Behavioral Therapy, with the aim of modifying recurring thoughts of low self-esteem, so that new goals, reference to well-being, could be set, so that this would recover joy and replace the episodes depressives that torment her. It should be noted that in order to continue with his evolution, the patient undertook to work on himself to opt for new and good habits in his life, since depression is a low state of mind that alters behavior to such a degree that if it is not constantly treated or evaluated can lead to suicidal thoughts and suicide attempts.